“An Effect That is Deeper Than Beating” Family Violence in Jordanian Women - Morse, Diane S (2012)
This study informs healthcare approaches to gender-based family violence through focus groups with Jordanian women. The authors conducted a thematic qualitative analysis of 12 focus groups among 70 married, divorced, or widowed women about their experiences and beliefs regarding family violence. Five themes relevant to healthcare providers were identified. Three of the themes addressed participant-perceived causes of gender-based family violence: 1) unmet gender role expectations, 2) stigma and social norms, and 3) extended family roles. The fourth theme reflects effects on victims. The fifth theme reflects protective qualities and help seeking behaviors. The themes identified in the analysis reveal multiple ways that gender-based family violence can contribute to health problems and that it can be kept secret by Jordanian women as patients. Potential clues are described for the violence which may not be typically explored in a medical encounter. Additional ways that Jordanian families may seek help from other family or clergy instead of police and family violence agencies are described. Implications of these results for healthcare providers who care both for Jordanians and Arab immigrants in Western cultures are discussed.